History with Geography (Gogol on the Way to the Holy Land) - Victor M. Guminsky (Studia Litterarum)
The article makes an attempt to specify the actual routes of Gogol’s sea voyage in the Mediterranean Sea on his way to the Holy Land in the beginning of 1848 and to analyze the available data about his possible routes (in comparison to other Russian pilgrims). The author attempts to verify the authenticity of some data shared by Gogol whose reputation of an inventor and hoaxer among his contemporaries was not accidental. The article questions the tentative Gogol’s pilgrimage to the Corfu Island (Kerkira) to pray before the relics of St. Spyridon of Trimython and an extraordinary event that happened there: a miracle that provided an evident proof against one Englishman’s skepticism who had suggested that the relics’ incorruptibility was fabricated. Gogol’s story about the “Englishman’s disgrace” was retold by two of his contemporaries, and these reports are acknowledged by some modern researchers as truthful. However, the author of this essay believes there are some reasons to mistrust these sources as accurate. The data used for this purpose was taken from the published materials and archive sources but also bears on factual information, such as distances between different geographical points and the average speed of steamships in the middle of the 19 th century.